Co-firing coal with wood pellets for U.S. electricity generation: A real options analysis. (June 2015) - Xian, Hui; Colson, Gregory; Mei, Bin; Wetzstein, Michael E.
Abstract: In contrast to EU, U.S. electric utilities are not employing the bioenergy technology of co-firing wood pellets with coal. This difference in employment patterns is explored within a real options analysis (ROA) for possible U.S. utilization of wood pellets, considering fuel-price series from 2009 to 2014. For analysis, these series are divided into two sub-periods based on different market conditions: Infancy (2009–2011) and Substitution (2012–2014). ROA indicates co-firing wood pellets with coal is feasible considering adoption during wood pellets' infancy, under low discount rates, and long power-plant lifespans. A portfolio effect of employing multiple fuels underlies this result. However, co-firing is not currently economically feasible. The different adoption decisions are likely a consequence of recent cheap and abundant U.S. natural gas. For co-fired wood pellets to be feasible, government incentives and/or a market increase in natural gas prices appear necessary. Highlights: Real options analysis indicates co-firing is not currently economically feasible within the U.S. The recent U.S. natural-gas boom is likely hindering the adoption of co-firing. For co-fired adoption, government incentives or an increase in natural-gas prices are necessary.